Self-Healing Thermoset Polyurethanes Driven by Host–Guest Interactions Between α-Cyclodextrin and Poly(ethylene glycol) Monomethyl Ether or Dodecanol Moieties - Riku Miyagawa; Mitsuhiro Shibata (Molecules)
Self-healing thermoset polymers have attracted significant attention because they contribute to resource and energy savings by extending their service life. The reactions between glycerol ethoxylate (GCE), α-cyclodextrin (α-CD), poly(ethylene glycol) monomethyl ether (MPEG), and hexamethylene diisocyanate (HDI) at molar ratios of GCE:α-CD:MPEG = a:b:c produced polyurethane networks (GCM-abc, abc = 311, 411, and 511) containing α-CD and MPEG as host and guest moieties, respectively. To compare this with GCM-411, 1-dodecanol (DN) was used instead of MPEG as a guest molecule to yield a polyurethane network (GCD-411). Dynamic mechanical analysis revealed the formation of a polymer network, and the loss tangent (tan δ) peak temperature (Tα) and crosslinking density (νe) decreased with increasing GCE fraction for GCMs, and the Tα and νe values of GCD were slightly higher than those of GCM-411. The tensile strength of the GCMs decreased with increasing GCE fraction, and the tensile strength of GCD-411 was slightly higher than that of GCM-411. All cured films were healed at room temperature for 24 h, and the healing efficiency (ησ), based on tensile strength, increased in the order of GCM-311 < GCM-411 < GCM-511 < GCD-411. When the healing temperature increased from room temperature to 80 °C, ησ increased from 24–38% to 45–62%. GCM-411 and GCD-411 were self-healed thrice by treatment at 80 °C, and ησ gradually decreased with each healing cycle.